Study on the reversal of epileptic drug resistance by tetramethylpyrazine in combination with carbamazepine through modulation of P-Glycoprotein expression in rat brain microvessel endothelial cell: Combining tetramethylpyrazine with carbamazepine reverses drug resistance in epilepsy - Qian, Xia; Deng, Yuqing; Zhong, Na; Li, Yuxuan; Wang, Junhua; Yan, Jinhua; Liu, Wei; Ye, Jinglei; Liu, Jingchao; Xiao, Guobei (Cellular and Molecular Biology, 2023)
The purpose of this study was to detect the changes of P-Glycoprotein (P-GP) expression in rat brain microvessel endothelial cell line RBE4 after the action of Tetramethylpyrazine (TMP) on Carbamazepine (CBZ), so as to clarify the potential mechanism of TMP combined with CBZ against intractable epilepsy drug resistance. The RBE4 cell line was utilized for in vitro analysis. Cells were divided into control, CBZ, and CBZ-TMP group. The expression of P-GP was assessed using Western blot and reverse transcription polymerase chain reaction (RT-PCR). Intracellular concentration of CBZ was measured through high-performance liquid chromatography (HPLC). The differential expression of mRNA was evaluated by RNA sequencing. The intracellular concentration of CBZ in the CBZ-TMP group was significantly higher than that in other groups. The expression of P-GP in the CBZ group was significantly higher than that in the control group, while in the CBZ&TMP group, it was significantly lower than that in the other groups. Comparative analysis also revealed some differentially expressed genes. Compared with the CBZ group, FAM106A, SLC3A2, TENM2, etc. were upregulated most significantly in the CBZ&TMP group. ZBTB10, WDR7, STARD13, etc. were downregulated most significantly. Results suggest that TMP increases the intracellular concentration of CBZ, downregulates the expression of P-GP increased by CBZ, and modulates related cellular metabolism and signaling pathways, thus reversing the drug resistance mechanism of intractable epilepsy, providing a theoretical basis for the combination of traditional Chinese medicine and antiepileptic drugs.